Dynamic translocation of stilbene synthase VpSTS29 from a Chinese wild Vitis species upon UV irradiation. (March 2019) - Ma, Fuli; Yao, Wenkong; Wang, Lei; Wang, Yuejin
Abstract: Stilbene phytoalexins derived from grapevine can be rapidly accumulated when exposed to an artificial UV-C treatment. However, the underlying mechanisms involved in this accumulation and translocation are unclear. Here, we describe an investigation of the influence of UV-C treatment on the dynamic subcellular distribution of a member of a stilbene synthase family VpSTS29 derived from Chinese wild Vitis pseudoreticulata W.T. Wang when over-expressed in V. vinifera L. cv. Thompson Seedless. Our results show that VpSTS29-GFP was accumulated at a relatively high level in roots and mature leaves of transgenic grape lines, and was predominantly distributed in the cytoplasm. When exposed to UV-C irradiation, VpSTS29 displayed UV-induced feature coupled with the accumulation of stilbene compounds. Notably, VpSTS29-GFP can be translocated from the cytoplasm into chloroplasts upon UV-irradiation. Leaves from the two VpSTS29-GFP -expressing lines displayed more serious UV damage, showing withering and marginal scorching phenotype, and decreased content of H2 O2, compared to the untransformed plant. Also, overexpression of VpSTS29 altered the expression of genes related to redox regulation, stilbene biosynthesis and light stimulus. Co-expression of VpSTS29-GFP with Glycolate oxidase 1 (myc- VpGLO1) confirmed the ability of stilbenes to decrease the content of H2 O2 in Arabidopsis mesophyll protoplasts. These results provide new insight into the biological functions and properties of stilbene synthase and its product in response to environmental stimulus. Graphical abstract: The biosynthesis of trans -resveratrol is catalysed by stilbene synthase using one p -coumaroyl-CoA and three malonyl-CoA as substrates in grape. Highlights: VpSTS29 accumulated to relatively high levels in both roots and mature leaves. VpSTS29 was translocated from the cytosol into chloroplasts after UV-C treatment. Accumulation both of VpSTS29 and of stilbenes was induced by UV-C treatment. Over-expression of VpSTS29 increased the sensitivity of grapes to UV-C treatment.